On The Realization of Current-Mode Integrator Using Current Conveyors - Muhammad Taher Abuelma'Atti (Active and Passive Electronic Components)
An improved analysis of a recently proposed current-mode integrator [1] is presented. The analysis includes the parasitic serial resistance on port X of the current conveyor. The feasibility of obtaining an error cancellation is considered.